Tumour biology of colorectal liver metastasis is a more important factor in survival than surgical margin clearance in the era of modern chemotherapy regimens. Issue 2 (9th July 2014) - Truant, Stéphanie; Séquier, Cédric; Leteurtre, Emmanuelle; Boleslawski, Emmanuel; Elamrani, Mehdi; Huet, Guillemette; Duhamel, Alain; Hebbar, Mohamed; Pruvot, François‐René
Abstract Background The aim of the authors was to reassess the impact of a positive surgical margin (R1) after a liver resection for colorectal liver metastases (CLMs) on survival in the era of modern chemotherapy, through their own experience and a literature review. Methods Inclusion criteria were: R1 or R0 resection with no local treatment modalities, extra‐hepatic metastases or other cancer. Results Among 337 patients operated between 2000 and 2010, 273 patients were eligible (214 R0/59 R1). The mean follow‐up was 43 ± 29 months. Compared with a R0 resection, a R1 resection offered a lower 5‐year overall (39.1% versus 54.2%, P = 0.010), disease‐free (15.2% versus 31.1%, P = 0.021) and progression‐free (i.e. time to the first non‐curable recurrence; 33.1% versus 47.3%, P = 0.033) survival rates. Metastases in the R1 group were more numerous, larger and more frequently synchronous. Independent factors of poor survival were: number, size and short‐time interval of CLM occurrence, N status, rectal primary, absence of adjuvant chemotherapy, but not a R1 resection. With the more‐systematic administration of chemotherapy since 2005, the intergroup difference in progression‐free survival disappeared (P = 0.264). Conclusion A R1 resection had no prognostic value per se but reflected a more severe disease. The recent change in the prognostic value of a R1 resection may be linked to the beneficial effect of chemotherapy.